On Clustering Algorithm Of Coverage Area Problems In Wireless Sensor Networks - Ismail Abdullah; Kalid Abdlkader Marsal (Scientific Federation, 2024)
Wireless sensor networks (WSN) has applications in many areas such as in surveillance, healthcare, national security, military and environmental monitoring. For WSNs, the coverage problem has proven to be one of the fundamental issues, because of which the sensor network's efficiency and capability are directly influenced. This also proved to be the most complicated area for research, which was to detect the maximal total of active nodes or sleep, specifically the node scheduling part, its business with the WSN being to determine the optimal coverage area at which exist the most number of active nodes that manage connectivity and coverage. The size of a WSN can be up to hundreds or maybe even thousands of sensor nodes. The corresponding deployment technique can be figured out if the placement of the sensors is exactly where they are needed. The lifespan of a WSN can be increased by efficient routing techniques, but the following research, for the most part, focuses on the length of the survival of networks, without bearing in mind the 'quality' of the network in its last or final iterations. In the following paper, the effect that changing the fitness cap used in the genetic algorithm has, on a WSN, in terms of lifespan and the quality of lifespan, is documented. For the proliferation of wireless sensor network, in different environments, an escalation in the lifetime of wireless sensors is mandatory, because among the basic issues concerning WSN is a successful effort to document the coverage of the number of target fields, while maximizing the lifetime of this network. In the case study, many algorithms have been proposed in the literature, in order to find the maximum number of disjoint or non-disjoint sets of sensor cover sets, we can see where one set can be active at any one time. The link between energy consumption and the radio bandwidth is requested to be hampered with, to escalate the lifespan of the sensors. An important problem in the wireless sensor networks is connectivity of the consumption of energy, because a network is linked for the communication of two active nodes. Because the information collected by the sensor nodes has to be repeated back to the data controllers or sinks, when the sensors are arranged, they deploy into a network that must be connected. In fact, the energy utilization or consumption of point coverage can be managed. In the following study, the radio bandwidth's energy consumption is the target under study, which in turn is predicted to optimize WSN.